(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2016)
Background: Sedation has become more common for children undergoing procedures in the emergency department, dentistry, and day care surgery. A desirable sedative agent has a rapid onset with short duration of action and is effective and safe. Midazolam as a sedative agent that fulfills these criteria. However controversy surrounds regarding its route of administration, particularly with respect to its ease of administration and patient acceptance. Although the oral route of administration is the most popular among pediatric surgeons and dentists, confrontation and frustration often arise when children refuse to accept the sedative medication. Objectives: To evaluate the outcome (satisfactory anxiolysis and smooth early parental separation) between oral midazolam (OM) and intranasal midazolam(INM)spray in children for conscious sedation before general anaesthesia. Methods: Children aged 1 6 years scheduled for routine elective surgery were included to receive midazolam as premedication drug. A total of 80 children were recruited consecutively. Of them 40 were randomly assigned to either single dose of 0.5 mg/kg via oral route (OM0) or 0.5 mg/kg of body weight by intranasal spray(INM). The outcome variables were smooth separation of children from their parents at the level of conscious sedation and time to smooth separation. Results: No change in sedation score was evident in first 3 minutes following midazolam administration. Then the sedation score of INM group increased sharply to assume a mean score of 2 at 9 minutes. No demonstrated change was further noted up to the end of observation. Meanwhile the sedation score of OM group began to increase steadily up to the end of observation when it assumed a mean score of 1.5. The INM group attained a good level of sedation much earlier than its OM counterpart. The mean sedation scores were significantly higher in the former group than those in the latter group. During the first 3 minutes of midazolam administration no change in anxiolysis was noted. Then the score began to increase in both the INM and OM groups, but INM group experienced a much faster increase than the OM group so that the former group reached a mean score of almost 3 and the latter group to a mean score of nearly 2 at 15 minutes interval. The levels of anxiolysis attained by the intranasal group were significantly higher compared to those attained by the oral midazolam group (table II).All but 1 children (97.5%) in the INM group were separated from their parents smoothly as opposed to 90% in the OM group (p = 0.148). In the INM group 12.8% of children were separated at 9 minutes, 69.2% from 10 12 minutes (over two-thirds) and 18% from 15 18 minutes. In the OM group 13.9% were separated at 15 minutes, about 39% at 18 21 minutes, 22.3% at 24 minutes and the rest 11.1% at 27 minutes after premedication. Overall more than 80% of the children in the INM group were separated at 9 12 minutes following midazolam administration when none of the children in the OM group was separated (p < 0.001). Complications like nasal irritation was staggeringly higher in the INM group shown on table IV. Conclusion: Despite the intranasal route causes a substantial proportion of children to suffer from nasal irritation, it is the preferred route over oral route, because intranasal route induces much faster sedation and anxiolysis and helps easy and smooth separation of children from their parents. Journal of Bangladesh Society of Anaesthesiologists 2014; 27(1): 17-23